STUDENTS’ PERCEPTION OF THE USE OF ChatGPT AS A WRITING ASSISTANT IN EFL CLASSROOM OF GRADE IX AT SMP NEGERI 10 PEMATANGSIANTAR - Tio Lestari Br Simanjuntak; Chritian Neni Purba; David Berthony Manalu; Irene Adryani Nababan (RADJA PUBLIKA, 2025)
The rapid advancement of technology, particularly artificial intelligence (AI), has transformed English language learning, including the development of students’ writing skills. ChatGPT, an AI-based language model, has increasingly been used as a writing assistant to help learners generate ideas, organize text structure, improve grammar, and expand vocabulary. This study aims to explore the perceptions of ninth-grade students at SMP Negeri 10 Pematangsiantar regarding the use of ChatGPT as a writing assistant in an English as a Foreign Language (EFL) classroom. Employing a qualitative descriptive approach with a case study design, the study investigates students’ perceived usefulness (PU) and perceived ease of use (PEOU), guided by the Technology Acceptance Model (TAM). Data were collected through open-ended essay questionnaires distributed to 28 students who had received direct instructional exposure to ChatGPT through guided writing activities. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the majority of students hold positive perceptions of ChatGPT. In terms of PU, students reported that ChatGPT effectively supported idea generation, improved writing structure and grammar, expanded vocabulary, enhanced writing quality, and increased their confidence in writing English texts. ChatGPT was also perceived as helpful in overcoming writing difficulties and completing academic tasks more efficiently. Regarding PEOU, students stated that ChatGPT was easy to learn, accessible through mobile devices, and provided clear and understandable responses. Many students also felt comfortable using it independently without teacher supervision. Nevertheless, several challenges were noted, such as unstable internet connectivity and difficulties in formulating appropriate prompts. Overall, the results indicate that ChatGPT is well-accepted by students and has the potential to serve as an effective tool for supporting English writing instruction at the junior high school level. The study recommends guided and ethical integration of ChatGPT in EFL classrooms to prevent overreliance and promote critical engagement with AI-generated content.